2015
DOI: 10.1093/ejcts/ezu520
|View full text |Cite
|
Sign up to set email alerts
|

FBN1 polymorphisms in patients with the dilatative pathology of the ascending thoracic aorta

Abstract: Our study provides evidence for the following: (i) FBN1 SNPs rs2118181, rs1036477, rs10519177, rs4774517, rs755251 may increase susceptibility to aortic dissections and (ii) FBN1 SNPs rs2118181, rs1036477 to the formation of aortic aneurysms. Thus, these SNPs might be considered as biomarkers for identifying patients at risk for ascending aortic aneurysm and aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Our data demonstrated that presence of rs2118181 minor allele significantly increased median TGF-β1 values, whereas such effect in rs10519177 was achieved only by homozygous carriers of two minor alleles. Moreover, these regularities correspond to the earlier reported associations between DPAA phenotypes and the genotyped FBN1 SNPs (6). According to these data, an additive minor allele model fitted best in describing the association between rs2118181 and aneurysm (odd ratio latent complex from proteolytic activation or whether FBN1 functions more directly in controlling assembly or stability of latent TGF-β1 complexes (14).…”
Section: Determination Of Genotypessupporting
confidence: 85%
See 1 more Smart Citation
“…Our data demonstrated that presence of rs2118181 minor allele significantly increased median TGF-β1 values, whereas such effect in rs10519177 was achieved only by homozygous carriers of two minor alleles. Moreover, these regularities correspond to the earlier reported associations between DPAA phenotypes and the genotyped FBN1 SNPs (6). According to these data, an additive minor allele model fitted best in describing the association between rs2118181 and aneurysm (odd ratio latent complex from proteolytic activation or whether FBN1 functions more directly in controlling assembly or stability of latent TGF-β1 complexes (14).…”
Section: Determination Of Genotypessupporting
confidence: 85%
“…This is the first report on the association between previously defined FBN1 SNPs (rs2118181 and rs10519177) linked with sporadic thoracic aorta aneurysm and dissection (6) and TGF-β1…”
Section: Discussionmentioning
confidence: 76%
“…It was reported that FN1 is hypoxia responsive in murine and human melanoma cells (Olbryt et al. 2011), and FBN1 is involved in heart disease, such as aortic aneurysm and aortic dissection (Lesauskaite et al. 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Among the genes related to arterial tortuosity, we searched for SNPs of genes that were studied in relation to arterial aneurysm and dissection, coronary artery disease, and peripheral artery disease. Of these, the following 4 SNPs were selected: rs2179357 ( SLC2A10 ) [15], rs2118181 ( FBN1 ) [16, 17], rs1036095 ( TGFBR2 ) [18, 19], and rs1800470 ( TGFB1 ) [7, 19]. In addition, 2 more SNPs were chosen, rs112735431 ( RNF213 ) [2, 4, 5, 20] and rs243865 ( MMP2 ) [13] because they have been studied in association with ICAS.…”
Section: Methodsmentioning
confidence: 99%